KESETIAAN DAN IDENTITAS SOSIAL KONSUMEN - Lerbin R Aritonang (Jurnal Manajemen., 2005)
The recent development in marketing strategy is changing from satisfaction to loyalty of consumers orientation because satisfying customer is not enough to reveal profit in the long term. Another consequence of th loyal consumers is heir social identity that will promote corporates product. So, it is important to define satisfaction, loyalty and socal identity and to identify their relationships.